2014
DOI: 10.1111/bph.12573
|View full text |Cite
|
Sign up to set email alerts
|

κ Opioid receptor ligands regulate angiogenesis in development and in tumours

Abstract: Opioid systems mainly regulate physiological functions such as pain, emotional tone and reward circuitry in neural tissues (brain and spinal cord). These systems are also found in extraneural tissues (ganglia, gut, spleen, stomach, lung, pancreas, liver, heart, blood and blood vessels), and recent studies have elucidated their roles in various organs. The current review focuses on the roles of opioid systems in blood vessels, especially angiogenesis, during development and tumour malignancy. The balance betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…They also confirmed that this inhibitory effect was mediated by hypoxia-induced mitochondrial p38 MAPK pathway inhibition [25]. Others [26] have argued that morphine also inhibits angiogenesis by suppressing VEGF signaling via the KOR, as KOR knockout mice grafted with Lewis lung carcinoma or B16 melanoma had more proliferation and enhanced angiogenesis compared to wild type mice [26]. In addition to its direct effect, morphine can also suppress the migration of leukocytes and reduce angiogenesis [27].…”
Section: Effect Of Morphine On Angiogenesismentioning
confidence: 81%
“…They also confirmed that this inhibitory effect was mediated by hypoxia-induced mitochondrial p38 MAPK pathway inhibition [25]. Others [26] have argued that morphine also inhibits angiogenesis by suppressing VEGF signaling via the KOR, as KOR knockout mice grafted with Lewis lung carcinoma or B16 melanoma had more proliferation and enhanced angiogenesis compared to wild type mice [26]. In addition to its direct effect, morphine can also suppress the migration of leukocytes and reduce angiogenesis [27].…”
Section: Effect Of Morphine On Angiogenesismentioning
confidence: 81%
“…Kappa agonists act on the pituitary to trigger the release of prolactin. KOR signaling is also important in the periphery, and KOR is expressed in the heart, vasculature, and gut (Pugsley, 2002;Yamamizu et al, 2015;Zhu et al, 1998). KOR and dynorphin null mice have an increase in vascular formation during embryogenesis (Yamamizu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that angiogenic activators play an important part in the growth and spread of tumors. Disturbance of the balance between endogenous activators such as vascular endothelial growth factor (VEGF) and inhibitors of angiogenesis in the tumor microenvironment strongly induce tumor angiogenesis (Yamamizu et al, 2015). Angiogenesis is a normal and vital process in growth and development as well as in wound healing.…”
Section: Discussionmentioning
confidence: 99%